Pengembangan PBL Integrated Bioenvironmentalscience App (BES App) untuk Pembelajaran Lingkungan - Winda Purnama Sari; Dwi Indra Aprilliandari (BIOEDUSCIENCE, 2021)
Background: Biology learning under the Covid-19 pandemic aimed to enhance educators' pedagogical competence by improving thinking abilities and producing results. One of the innovations intended to facilitate environmental learning is the BioEnviroScience App (BES App) for learning environmental science materials, specifically in the sub-environmental changes that occurred in the Province of the Bangka Belitung Islands. This media is integrated with Problem Based Learning (PBL) characteristics to guide the learning, allowing students to obtain learning experiences and make learning meaningful. Methods: This development design uses D&DR, which consists of six stages: 1) identifying the problem, 2) describing the objectives, 3) designing and developing the artifact, 4) testing the artifact, 5) evaluating testing results, and 6) communicating the testing findings. The feasibility test of the produced medium comprises a material, biological, and media specialists and is supported by peer review. A questionnaire was used to obtain data, which was examined quantitatively. Results: The material aspect of the feasibility test received 91.08% in the excellent category, the learning aspect of biology received 85.03% in the excellent category, and the media aspect received 89.08% in the excellent category. Conclusion: BES App deserves to be implemented on a large scale in several high schools in Pangkalpinang City.